Response of slowly adapting articular mechanoreceptors in the cat knee joint to alterations in intra-articular volume. Issue 2 (April 1984) - Wood, L; Ferrell, W R
Abstract : Recordings were obtained from slowly adapting mechanoreceptors innervating the posterior aspect of the cat knee joint capsule. It was observed that, with rising intra-articular volume, initially both intra-articular pressure and the neural discharge increased. This increase was dependent on the rate of fluid accumulation within the joint. However, the joint nerve discharge invariably levelled out despite increasing intra-articular volume and pressure. This suggests that there exists some limit to capsular distension in the posterior joint region beyond which fluid is diverted to other areas of the knee joint.